Structure-function relationship for the highly toxic crotoxin from Crotalus durissus terrificus - Mascarenhas, Yvonne P.; Stouten, Pieter F.W.; Beltran, José R. [UNESP]; Laure, Carlos J.; Vriend, Gerrit (Springer Nature, 1992)
The three-dimensional structure of the highly toxic crotoxin from Crotalus durissus terrificus was modelled based on sequence analysis and the refined structure of calcium-free phospholipase of Crotalus atrox venom. Small-angle x-ray scattering experiments were performed on aqueous solutions of crotoxin. The radial distribution function derived from these scattering experiments and the one calculated from the model structure are in good agreement. Crotoxin consists of a basic and an acidic subunit. The model strongly suggests that the overall folding motif of phospholipases has been preserved in both subunits. The basic domain has an intact active site. The residues that are expected to contact the lipid tails of the phospholipid are different from other phospholipases, but they are all hydrophobic. The acidic domain consists of three independent chains interconnected by disulfide bonds. Compared to other phospholipases the active site for the greater part has been preserved in this domain, but it is not very well shielded from solvent. Most residues normally in contact with the lipid tails of the phospholipid are missing, which might explain the acidic subunit's lack of phospholipase activity. A homology between the third chain of the acidic domain and neurophysins suggests that the acidic domain may act as a chaperone for the basic domain. © 1992 Springer-Verlag.
Keywords: Crotoxin; Modelling by homology; Structure-function relationship; X-ray scattering